Pterostilbene induces pyroptosis in mouse breast cancer cells through the caspase-3/Gasdermin E signaling pathway and reshapes the tumor immune microenvironment - Xiaoxia Huang; Wenhui Yang; Xinyi Hu; Li Peng; Jing Dong; Lin Li (Translational Oncology)
There is increasing evidence that the intake of specific dietary supplements may reduce the risk of breast cancer. Pterostilbene (PTE), a naturally occurring stilbene compound that is widely found in berries, induced pyroptosis in EMT6 and 4T1 cells in a dose-dependent manner. Additionally, si Gasdermin E (GSDME) and Z-DEVD-FMK (a caspase-3 enzymatic activity inhibitor) significantly inhibited PTE-induced pyroptosis in these cells. These findings suggest that PTE induces pyroptosis in mouse breast cancer cells through the caspase-3/GSDME signaling pathway. Mice with transplanted EMT6 breast tumors were established to investigate the antitumor activity of PTE in vivo. The results showed that PTE prevented and inhibited breast tumor growth in a dose-dependent manner. GO and KEGG annotation analysis showed that lots of differential genes were concentrated in the immune system. To further verify whether PTE inhibits tumors by reshaping the tumor immune microenvironment (TIME), we detected the proportions of Th cells, CTL cells, NK cells, MDSC cells, TAMs, Treg cells and B cells in the mouse peripheral blood, spleen and breast tumors. And PTE was found to up-regulate the proportions of antitumor immune cells and down-regulate the proportions of immunosuppressive cells. In conclusion, PTE inhibited breast tumor growth by introducing breast caner cells pyroptosis, enhancing antitumor immunity and reshaping the TIME. Consequently, this study has significant implications for the development of PTE and PTE-containing functional foods, dietary supplements, immunomodulatory drugs, and breast cancer treatment adjuvants.